Social, Legal and Economic Implications for the Implementation of an Intelligent Wound Plaster in Outpatient Care - Enste, Peter; Kucharski, Alexander Bajwa (Frontiers in Political Science, 2021)
Background: The care of chronic wounds is one of the core tasks of inpatient and outpatient care. The correct timing of changes has a significant impact on the positive course of wound healing. The VulnusMON project developed an intelligent wound plaster to determine the optimum time to change the plaster in hospital. Against the background of implementing the solution also in the outpatient sector, this article focuses on the following research questions: What is the legal framework for wound care in outpatient care? What are the differences in wound care between inpatient and outpatient care? What obstacles and barriers arise for the VulnusMON project when it is implemented in the outpatient sector? Can initial economic estimates be made for the transfer to the outpatient sector? Method: Due to the complexity of the different research questions, a mixed method design was used. The qualitative part of the study includes both focus groups and expert interviews. As part of the quantitative analysis, a data set on outpatient wound care was analyzed (n = 463). Results: In summary, it can be stated that the project VulnusMON and its intelligent wound plaster, which aims to determine the ideal time to change a wound plaster is viewed very positively by the professionals. However, there are a number of barriers that inhibit the potential transfer of the new digital solution to the outpatient setting. From an economic point of view, implementation in the outpatient sector makes sense, as travel times can be reduced. However, the study also points out important social implications, that pose several challenges for the actual transfer of the plaster to the outpatient sector.